PERFORMING COMPLEX MATHEMATICAL CALCULATIONS IN PYTHON USING THE SYMPY LIBRARY - Raupova M. H.; Xasanova M. F. (Journal Park Publishing, 2024)
This article describes the use and importance of Python's Sympy library. For users new to Python, here are some helpful tips on how to install and use the SymPy library. A number of composed mathematical examples are implemented in Python using the SymPy library.
Keywords: SymPy, Python, integrate, differential, dsolve.